A flame-retardant PP material for battery shell and preparation method thereof

By using hollow porous titanium dioxide fibers in lithium battery housing materials to form fibrous flame retardant chemical reactions with magnesium hydroxide, phosphorus and nitrogen, the problem of flammability and explosion of lithium battery housing is solved, and the flame retardant performance is improved. Mechanical properties ensure battery safety.

CN118006047BActive Publication Date: 2024-12-13WUJIANG BODA ELECTRONICS TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410259728.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-07
Publication Date
2024-12-13
Estimated Expiration
2044-03-07

AI Technical Summary

Technical Problem

The lithium battery housing material is prone to combust and explosion under adverse use conditions, resulting in safety hazards. The existing PP materials have low oxygen index and are flammable.

Method used

Hollow porous titanium dioxide fibers with magnesium hydroxide, phosphorus and nitrogen through specific chemical reactions to form fibrous flame retardant, combined with 3,4-dihydroxyphenylalanine and oxychloride, and prepared by ultrasonic reaction and melt blending technology. Flame retardant PP material.

Benefits of technology

It significantly improves the flame retardant performance of the battery case, prevents combustion and explosion caused by thermal runaway, enhances the mechanical properties, and meets the safety and mechanical requirements of the battery case.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a method for preparing a flame-retardant PP material for a battery shell, comprising the following steps: S1. preparing titanium dioxide fiber filled with magnesium hydroxide; S2. adding the titanium dioxide fiber coated with magnesium hydroxide prepared in step S1 to dimethyl sulfoxide, stirring at a certain temperature, then adding sodium bisulfate, stirring and adding 3,4-dihydroxyphenylalanine, reacting under anaerobic conditions to obtain surface-modified fiber; S3. adding the surface-modified fiber prepared in step S2 to tetrahydrofuran containing phosphorus oxychloride, adding pyridine, and after ultrasonic reaction, dripping a tetrahydrofuran solution containing 4,4-diaminodiphenylmethane, and reacting to obtain P / N modified fiber; S4. melt blending PP, P / N modified fiber and antioxidant to obtain flame-retardant PP material. The present invention uses two inorganic flame retardants to compound in a specific manner, and surface-modify and add phosphorus and nitrogen, and apply them to PP materials to improve the flame retardant properties of battery shells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polymers, and in particular to a flame-retardant PP material for a battery shell and a preparation method thereof. Background Art

[0002] Lithium-ion batteries (lithium batteries) are favored by the industry for their high specific energy, long cycle life, low self-discharge, no memory effect and green environmental protection. Lithium batteries have gradually replaced the lead-acid battery market as a new type of green energy. As its application areas continue to expand, the safety of lithium battery use, especially the safety of large-capacity power lithium batteries, has become a focus of attention.

[0003] Lithium batteries are made of highly active materials, which are very likely to undergo violent chemical reactions under heat conditions, generating a large amount of heat, and even leading to "thermal runaway", causing rapid temperature rise inside the battery. Especially when the battery is abused (such as short circuit, vibration, extrusion, strong impact, over-discharge and over-charge, etc.), the battery will smoke, catch fire, explode, and even cause injuries to people. The battery shell is a pressure-bearing carrier inside and outside the battery. Its flame retardancy and impact resistance play a vital role in the battery when dangerous conditions occur.

[0004] At present, plastic case lithium batteries generally use polypropylene (PP) as the battery shell material. PP material has the advantages of good heat resistance and chemical solvent corrosion resistance. It is one of the few plastic materials that can withstand electrolyte corrosion, so it is currently a commonly used battery shell material in the industry. However, PP material has a low oxygen index, is extremely easy to burn in the air, releases a lot of heat when burning, and has a very fast flame propagation speed, which buries certain hidden dangers for battery safety. Adding flame retardants to PP materials to improve the flame retardant properties of PP materials themselves can effectively prevent the shell from burning caused by "thermal runaway" inside the battery, and ensure that the battery shell does not burn or explode in adverse environments such as abuse. Summary of the invention

[0005] Technical problem to be solved: The purpose of the present invention is to provide a flame-retardant PP material for a battery shell and a preparation method thereof, which uses two inorganic flame retardants to compound in a specific manner, and surface-modify them by adding phosphorus and nitrogen, and apply them to PP materials to improve the flame retardant properties of the battery shell.

[0006] Technical solution: A method for preparing a flame-retardant PP material for a battery shell, comprising the following steps:

[0007] S1. adding the hollow porous titanium dioxide fiber to water and uniformly dispersing it by ultrasonication to obtain a titanium dioxide fiber suspension, adding a magnesium chloride solution to the suspension, and stirring at a constant temperature until the magnesium chloride penetrates into the surface and gaps of the titanium dioxide fiber, and then adding ammonia water to react to obtain a titanium dioxide fiber filled with magnesium hydroxide;

[0008] S2. adding the titanium dioxide fiber coated with magnesium hydroxide prepared in step S1 to dimethyl sulfoxide, stirring at a certain temperature, then adding sodium bisulfate, stirring and then adding 3,4-dihydroxyphenylalanine, reacting under anaerobic conditions to obtain a surface-modified fiber;

[0009] S3. adding the surface-modified fiber prepared in step S2 to tetrahydrofuran containing phosphorus oxychloride, and adding pyridine, and after ultrasonic reaction, adding dropwise a tetrahydrofuran solution containing 4,4-diaminodiphenylmethane, and reacting at room temperature to obtain a P / N-modified fiber;

[0010] S4. Add PP, P / N modified fiber and antioxidant into the torque rheometer in a certain proportion for melt blending to obtain flame retardant PP material.

[0011] Preferably, the method for preparing the hollow porous titanium dioxide fiber comprises the following steps:

[0012] S11. The butyl titanate was dissolved in acetone, stirred evenly, and polyvinyl pyrrolidone was added and stirred to dissolve to obtain a butyl titanate solution;

[0013] S12. Remove the glue on the surface of the cotton fiber with a sodium hydroxide solution, then acidify it with a low concentration of acid, add sodium chloroacetate and 1,3-pentanediamine to the acidified cotton fiber, stir for reaction, add the butyl titanate solution prepared in step S1, stir and ultrasonicate, filter, dry and calcine to obtain a hollow porous titanium dioxide fiber.

[0014] Preferably, in step S11, the mass ratio of butyl titanate, polyvinyl pyrrolidone and acetone is 4-8:0.5-1:8-15.

[0015] Preferably, in step S12, the mass ratio of cotton fiber, sodium chloroacetate, 1,3-pentanediamine and butyl titanate solution is 10:1-2:0.8-1.2:15-20, the calcination parameters are heating at room temperature, a heating rate of 1-1.5°C / min, a termination temperature of 650-720°C, and calcination is continued for 2-3h after reaching the termination temperature.

[0016] Preferably, in step S1, the concentration of magnesium chloride is 1-1.2 mol / L, the concentration of ammonia water is 1.2-1.6 mol / L, the temperature of constant temperature stirring is 25-35° C., and the reaction time is 30-45 min.

[0017] Preferably, in step S2, the stirring temperature is 80-100° C. and the reaction time is 10-30 h.

[0018] Preferably, in the step S3, the mass ratio of the surface-modified fiber, phosphorus oxychloride, 4,4-diaminodiphenylmethane and pyridine is 5-10:3-8:6-12:2-3.

[0019] Preferably, the ultrasonic reaction time in step S3 is 1-3 h, and the room temperature reaction time is 10-30 h.

[0020] Preferably, in step S4, the mass ratio of P, P / N modified fiber and antioxidant is 100:20-35:0.2-0.8; the blending temperature is 175-190° C., the torque speed is 40-60 r / min, and the blending time is 8-15 min.

[0021] The flame-retardant PP material for the battery shell prepared by the above preparation method.

[0022] Beneficial effects: The flame-retardant PP material for the battery shell of the present invention has the following advantages:

[0023] In the present invention, a hollow, porous titanium dioxide fiber is first prepared. Titanium dioxide itself is flame retardant. It is prepared into a hollow, porous form to facilitate the generation of magnesium hydroxide in the hollow structure. Magnesium chloride reacts with ammonia water, i.e., MgCl 2 +2NH 4 OH→Mg(OH) 2 ↓+2NH 4 Cl, thus a titanium dioxide fiber filled with and coated with magnesium hydroxide can be obtained, which synergistically achieves a better flame retardant effect;

[0024] In the present invention, 3,4-dihydroxyphenylalanine is grafted on the surface of the prepared titanium dioxide fiber filled with magnesium hydroxide, and the hydroxyl structure on the benzene ring of 3,4-dihydroxyphenylalanine and phosphorus oxychloride and 4,4-diaminodiphenylmethane are combined through chemical bonds such as hydrogen bonding to prepare a flame retardant integrating acid source, carbon source and gas source;

[0025] In the present invention, the morphological structure of the flame retardant is designed to be fibrous rather than ordinary granular because the fibrous flame retardant can achieve the effect of mechanical reinforcement while being flame retardant. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments:

[0027] Example 1

[0028] A method for preparing a flame-retardant PP material for a battery shell comprises the following steps:

[0029] S1. Add the hollow porous titanium dioxide fiber to water and disperse it evenly by ultrasonic to obtain a titanium dioxide fiber suspension, add a magnesium chloride solution with a concentration of 1 mol / L to the suspension, and stir at a constant temperature of 25°C until the magnesium chloride penetrates into the surface and gaps of the titanium dioxide fiber, then add ammonia water with a concentration of 1.6 mol / L to react for 45 minutes to obtain titanium dioxide fiber filled with magnesium hydroxide;

[0030] S2. adding the titanium dioxide fiber coated with magnesium hydroxide prepared in step S1 to dimethyl sulfoxide, stirring at 80° C., then adding sodium bisulfate, stirring, and then adding 3,4-dihydroxyphenylalanine, and reacting under anaerobic conditions for 30 hours to obtain surface-modified fibers;

[0031] S3. adding the surface-modified fiber prepared in step S2 to tetrahydrofuran containing phosphorus oxychloride, and adding pyridine, after ultrasonic reaction for 1 hour, dropwise adding a tetrahydrofuran solution containing 4,4-diaminodiphenylmethane, the mass ratio of the surface-modified fiber, phosphorus oxychloride, 4,4-diaminodiphenylmethane and pyridine being 5:3:6:2, and reacting at room temperature for 10 hours to obtain a P / N-modified fiber;

[0032] S4. The PP, P / N modified fibers and antioxidants were mixed in a mass ratio of 100:20:0.8 and added to a torque rheometer for melt blending. The blending temperature was 175°C, the torque speed was 60r / min, and the blending time was 15min to obtain a flame-retardant PP material;

[0033] The method for preparing the hollow porous titanium dioxide fiber comprises the following steps:

[0034] S11. Butyl titanate was dissolved in acetone and stirred, and then polyvinyl pyrrolidone, butyl titanate, polyvinyl pyrrolidone and acetone were added in a mass ratio of 4:0.5:8, and stirred to dissolve to obtain a butyl titanate solution;

[0035] S12. Use sodium hydroxide solution to remove the glue on the surface of cotton fiber, and then acidify it with low concentration acid, add sodium chloroacetate and 1,3-pentanediamine to the acidified cotton fiber, stir for reaction, and then add the butyl titanate solution prepared in step S1, the mass ratio of cotton fiber, sodium chloroacetate, 1,3-pentanediamine and butyl titanate solution is 10:1:0.8:15, stir and ultrasonicate, filter, dry and calcine, the calcination parameters are heating at room temperature, the heating rate is 1°C / min, the end temperature is 650°C, and the calcination is continued for 3 hours after reaching the end temperature to obtain hollow porous titanium dioxide fiber.

[0036] Example 2

[0037] A method for preparing a flame-retardant PP material for a battery shell comprises the following steps:

[0038] S1. Add the hollow porous titanium dioxide fiber to water and disperse it evenly by ultrasonic to obtain a titanium dioxide fiber suspension, add a magnesium chloride solution with a concentration of 1.2 mol / L to the suspension, and stir at a constant temperature of 35°C until the magnesium chloride penetrates into the surface and gaps of the titanium dioxide fiber, then add ammonia water with a concentration of 1.6 mol / L to react for 30 minutes to obtain titanium dioxide fiber filled with magnesium hydroxide;

[0039] S2. adding the titanium dioxide fiber coated with magnesium hydroxide prepared in step S1 to dimethyl sulfoxide, stirring at 100° C., then adding sodium bisulfate, stirring, and then adding 3,4-dihydroxyphenylalanine, and reacting under anaerobic conditions for 10 hours to obtain surface-modified fibers;

[0040] S3. adding the surface-modified fiber prepared in step S2 to tetrahydrofuran containing phosphorus oxychloride, and adding pyridine, after ultrasonic reaction for 3 hours, dropwise adding a tetrahydrofuran solution containing 4,4-diaminodiphenylmethane, the mass ratio of the surface-modified fiber, phosphorus oxychloride, 4,4-diaminodiphenylmethane and pyridine being 10:8:12:3, and reacting at room temperature for 30 hours to obtain a P / N-modified fiber;

[0041] S4. The PP, P / N modified fibers and antioxidants were mixed in a mass ratio of 100:25:0.2 and added to a torque rheometer for melt blending. The blending temperature was 190 ° C, the torque speed was 40 r / min, and the blending time was 8 min to obtain a flame retardant PP material;

[0042] The method for preparing the hollow porous titanium dioxide fiber comprises the following steps:

[0043] S11. The butyl titanate was dissolved in acetone, stirred, and then polyvinyl pyrrolidone, butyl titanate, the mass ratio of polyvinyl pyrrolidone and acetone was 8:1:15, stirred and dissolved to obtain a butyl titanate solution;

[0044] S12. Use sodium hydroxide solution to remove the glue on the surface of cotton fiber, and then acidify it with low concentration acid, add sodium chloroacetate and 1,3-pentanediamine to the acidified cotton fiber, stir for reaction, and then add the butyl titanate solution prepared in step S1, the mass ratio of cotton fiber, sodium chloroacetate, 1,3-pentanediamine and butyl titanate solution is 10:2:1.2:20, stir and ultrasonicate, filter, dry and calcine, the calcination parameters are heating at room temperature, the heating rate is 1.5℃ / min, the end temperature is 720℃, and the calcination is continued for 2h after reaching the end temperature to obtain hollow porous titanium dioxide fiber.

[0045] Example 3

[0046] A method for preparing a flame-retardant PP material for a battery shell comprises the following steps:

[0047] S1. Add the hollow porous titanium dioxide fiber to water and disperse it evenly by ultrasonic to obtain a titanium dioxide fiber suspension, add a magnesium chloride solution with a concentration of 1 mol / L to the suspension, and stir at a constant temperature of 28°C until the magnesium chloride penetrates into the surface and gaps of the titanium dioxide fiber, then add ammonia water with a concentration of 1.3 mol / L to react for 35 min to obtain titanium dioxide fiber filled with magnesium hydroxide;

[0048] S2. adding the titanium dioxide fiber coated with magnesium hydroxide prepared in step S1 to dimethyl sulfoxide, stirring at 85° C., then adding sodium bisulfate, stirring, and then adding 3,4-dihydroxyphenylalanine, and reacting under anaerobic conditions for 25 hours to obtain surface-modified fibers;

[0049] S3. The surface-modified fiber prepared in step S2 is added to tetrahydrofuran containing phosphorus oxychloride, and pyridine is added. After ultrasonic reaction for 1.5 hours, a tetrahydrofuran solution containing 4,4-diaminodiphenylmethane is added dropwise, and the mass ratio of the surface-modified fiber, phosphorus oxychloride, 4,4-diaminodiphenylmethane and pyridine is 6:4:10:2. The reaction is carried out at room temperature for 15 hours to obtain a P / N-modified fiber;

[0050] S4. The PP, P / N modified fibers and antioxidants were mixed in a mass ratio of 100:30:0.4 and added to a torque rheometer for melt blending. The blending temperature was 190°C, the torque speed was 45r / min, and the blending time was 10min to obtain a flame-retardant PP material;

[0051] The method for preparing the hollow porous titanium dioxide fiber comprises the following steps:

[0052] S11. The butyl titanate was dissolved in acetone, stirred, and then polyvinyl pyrrolidone, butyl titanate, the mass ratio of polyvinyl pyrrolidone and acetone was 5:0.6:9, stirred and dissolved to obtain a butyl titanate solution;

[0053] S12. Use sodium hydroxide solution to remove the glue on the surface of the cotton fiber, and then acidify it with low concentration acid. Add sodium chloroacetate and 1,3-pentanediamine to the acidified cotton fiber, stir for reaction, and then add the butyl titanate solution prepared in step S1. The mass ratio of cotton fiber, sodium chloroacetate, 1,3-pentanediamine and butyl titanate solution is 10:1.2:0.9:15. Stir and ultrasonicate, filter, dry and calcine. The calcination parameters are heating at room temperature, the heating rate is 1°C / min, the end temperature is 660°C, and the calcination is continued for 2 hours after reaching the end temperature to obtain hollow porous titanium dioxide fiber.

[0054] Example 4

[0055] A method for preparing a flame-retardant PP material for a battery shell comprises the following steps:

[0056] S1. Add the hollow porous titanium dioxide fiber to water and disperse it evenly by ultrasonic to obtain a titanium dioxide fiber suspension, add a magnesium chloride solution with a concentration of 1.2 mol / L to the suspension, and stir at a constant temperature of 30°C until the magnesium chloride penetrates into the surface and gaps of the titanium dioxide fiber, then add ammonia water with a concentration of 1.5 mol / L to react for 40 min to obtain titanium dioxide fiber filled with magnesium hydroxide;

[0057] S2. adding the titanium dioxide fiber coated with magnesium hydroxide prepared in step S1 to dimethyl sulfoxide, stirring at 95° C., then adding sodium bisulfate, stirring, and then adding 3,4-dihydroxyphenylalanine, and reacting under anaerobic conditions for 15 hours to obtain surface-modified fibers;

[0058] S3. The surface-modified fiber prepared in step S2 is added to tetrahydrofuran containing phosphorus oxychloride, and pyridine is added. After ultrasonic reaction for 2.5 hours, a tetrahydrofuran solution containing 4,4-diaminodiphenylmethane is added dropwise, and the mass ratio of the surface-modified fiber, phosphorus oxychloride, 4,4-diaminodiphenylmethane and pyridine is 9:7:8:3. The reaction is carried out at room temperature for 25 hours to obtain a P / N-modified fiber;

[0059] S4. The PP, P / N modified fibers and antioxidants were mixed in a mass ratio of 100:35:0.6 and added to a torque rheometer for melt blending. The blending temperature was 180°C, the torque speed was 55 r / min, and the blending time was 12 min to obtain a flame retardant PP material;

[0060] The method for preparing the hollow porous titanium dioxide fiber comprises the following steps:

[0061] S11. Butyl titanate was dissolved in acetone, stirred, and then polyvinyl pyrrolidone, butyl titanate, the mass ratio of polyvinyl pyrrolidone and acetone was 7:0.9:14, stirred and dissolved to obtain a butyl titanate solution;

[0062] S12. Use sodium hydroxide solution to remove the glue on the surface of cotton fiber, and then acidify it with low concentration acid. Add sodium chloroacetate and 1,3-pentanediamine to the acidified cotton fiber, stir for reaction, and then add the butyl titanate solution prepared in step S1. The mass ratio of cotton fiber, sodium chloroacetate, 1,3-pentanediamine and butyl titanate solution is 10:1.6:1.1:20. Stir and ultrasonicate, filter, dry and calcine. The calcination parameters are heating at room temperature, the heating rate is 1.5℃ / min, the end temperature is 700℃, and the calcination is continued for 3h after reaching the end temperature to obtain hollow porous titanium dioxide fiber.

[0063] Example 5

[0064] A method for preparing a flame-retardant PP material for a battery shell comprises the following steps:

[0065] S1. Add the hollow porous titanium dioxide fiber to water and disperse it evenly by ultrasonic to obtain a titanium dioxide fiber suspension, add a magnesium chloride solution with a concentration of 1.2 mol / L to the suspension, and stir at a constant temperature of 30°C until the magnesium chloride penetrates into the surface and gaps of the titanium dioxide fiber, then add ammonia water with a concentration of 1.5 mol / L to react for 40 min to obtain titanium dioxide fiber filled with magnesium hydroxide;

[0066] S2. adding the titanium dioxide fiber coated with magnesium hydroxide prepared in step S1 to dimethyl sulfoxide, stirring at 90° C., then adding sodium bisulfate, stirring, and then adding 3,4-dihydroxyphenylalanine, and reacting under anaerobic conditions for 20 hours to obtain surface-modified fibers;

[0067] S3. The surface-modified fiber prepared in step S2 is added to tetrahydrofuran containing phosphorus oxychloride, and pyridine is added. After ultrasonic reaction for 2 hours, a tetrahydrofuran solution containing 4,4-diaminodiphenylmethane is added dropwise, and the mass ratio of the surface-modified fiber, phosphorus oxychloride, 4,4-diaminodiphenylmethane and pyridine is 8:6:9:2.5. The reaction is carried out at room temperature for 20 hours to obtain a P / N-modified fiber;

[0068] S4. The PP, P / N modified fibers and antioxidants were mixed in a mass ratio of 100:35:0.5 and added to a torque rheometer for melt blending. The blending temperature was 188°C, the torque speed was 50r / min, and the blending time was 12min to obtain a flame-retardant PP material;

[0069] The method for preparing the hollow porous titanium dioxide fiber comprises the following steps:

[0070] S11. The butyl titanate was dissolved in acetone, stirred, and then polyvinyl pyrrolidone, butyl titanate, the mass ratio of polyvinyl pyrrolidone and acetone was 6:0.8:12, stirred and dissolved to obtain a butyl titanate solution;

[0071] S12. Use sodium hydroxide solution to remove the glue on the surface of the cotton fiber, and then acidify it with low concentration acid. Add sodium chloroacetate and 1,3-pentanediamine to the acidified cotton fiber, stir for reaction, and then add the butyl titanate solution prepared in step S1. The mass ratio of cotton fiber, sodium chloroacetate, 1,3-pentanediamine and butyl titanate solution is 10:1.4:1:18. Stir and ultrasonicate, filter, dry and calcine. The calcination parameters are heating at room temperature, the heating rate is 1.2 / min, the end temperature is 680°C, and the calcination is continued for 2.5 hours after reaching the end temperature to obtain hollow porous titanium dioxide fiber.

[0072] Comparative Example 1

[0073] A method for preparing a flame-retardant PP material for a battery shell comprises the following steps:

[0074] S1. The butyl titanate was dissolved in acetone, stirred, and then polyvinyl pyrrolidone, butyl titanate, the mass ratio of polyvinyl pyrrolidone and acetone was 6:0.8:12, stirred and dissolved to obtain a butyl titanate solution;

[0075] S2. Remove the glue on the surface of the cotton fiber with a sodium hydroxide solution, then acidify it with a low concentration of acid, add sodium chloroacetate and 1,3-pentanediamine to the acidified cotton fiber, stir and react, then add the butyl titanate solution prepared in step S1, the mass ratio of cotton fiber, sodium chloroacetate, 1,3-pentanediamine and butyl titanate solution is 10:1.4:1:18, stir and ultrasonicate, filter, dry and calcine, the calcination parameters are heating at room temperature, the heating rate is 1.2 / min, the end temperature is 680°C, and the calcination is continued for 2.5h after reaching the end temperature to obtain a hollow porous titanium dioxide fiber;

[0076] S3. The hollow porous titanium dioxide fiber is added to water and ultrasonically dispersed to obtain a titanium dioxide fiber suspension, a 1.2 mol / L magnesium chloride solution is added to the suspension, and the suspension is stirred at a constant temperature of 30°C until the magnesium chloride penetrates into the surface and gaps of the titanium dioxide fiber, and then a 1.5 mol / L ammonia water is added to react for 40 min to obtain titanium dioxide fibers filled with and coated with magnesium hydroxide;

[0077] S4. PP, titanium dioxide fiber coated with magnesium hydroxide and antioxidant were mixed in a mass ratio of 100:35:0.5 and added into a torque rheometer for melt blending. The blending temperature was 188° C., the torque speed was 50 r / min, and the blending time was 12 min to obtain a flame-retardant PP material.

[0078] Comparative Example 2

[0079] A method for preparing a flame-retardant PP material for a battery shell comprises the following steps:

[0080] S1. Add the hollow porous titanium dioxide particles to water and disperse them evenly by ultrasonication to obtain a titanium dioxide particle suspension, add a 1.2 mol / L magnesium chloride solution to the suspension, and stir at a constant temperature of 30°C until the magnesium chloride penetrates into the surface and gaps of the titanium dioxide fibers, then add 1.5 mol / L ammonia water to react for 40 min to obtain titanium dioxide particles filled with and coated with magnesium hydroxide;

[0081] S2. The titanium dioxide particles coated with magnesium hydroxide prepared in step S1 are added to dimethyl sulfoxide, stirred at 95° C., and then sodium bisulfate is added. After stirring, 3,4-dihydroxyphenylalanine is added, and the mixture is reacted under anaerobic conditions for 15 hours to obtain surface-modified particles;

[0082] S3. The surface-modified microparticles prepared in step S2 are added to tetrahydrofuran containing phosphorus oxychloride, and pyridine is added. After ultrasonic reaction for 2.5 hours, a tetrahydrofuran solution containing 4,4-diaminodiphenylmethane is added dropwise. The mass ratio of the surface-modified microparticles, phosphorus oxychloride, 4,4-diaminodiphenylmethane and pyridine is 9:7:8:3. The reaction is carried out at room temperature for 25 hours to obtain P / N-modified microparticles.

[0083] S4. PP, P / N modified particles and antioxidant were mixed in a mass ratio of 100:30:0.6 and added into a torque rheometer for melt blending. The blending temperature was 180°C, the torque speed was 60 r / min, and the blending time was 15 min to obtain a flame retardant PP material.

[0084] Comparative Example 3

[0085] A method for preparing a flame-retardant PP material for a battery shell comprises the following steps:

[0086] S1. The butyl titanate was dissolved in acetone, stirred, and then polyvinyl pyrrolidone, butyl titanate, the mass ratio of polyvinyl pyrrolidone and acetone was 8:1:15, stirred and dissolved to obtain a butyl titanate solution;

[0087] S2. Remove the glue on the surface of the cotton fiber with a sodium hydroxide solution, then acidify it with a low concentration of acid, add sodium chloroacetate and 1,3-pentanediamine to the acidified cotton fiber, stir and react, then add the butyl titanate solution prepared in step S1, the mass ratio of cotton fiber, sodium chloroacetate, 1,3-pentanediamine and butyl titanate solution is 10:2:1.2:20, stir and ultrasonicate, filter, dry and calcine, the calcination parameters are heating at room temperature, the heating rate is 1.5°C / min, the end temperature is 720°C, and the calcination is continued for 2h after reaching the end temperature to obtain a hollow porous titanium dioxide fiber;

[0088] S3. The hollow porous titanium dioxide fiber prepared in step S2 is added to dimethyl sulfoxide, stirred at 100° C., and then sodium bisulfate is added. After stirring, 3,4-dihydroxyphenylalanine is added, and the mixture is reacted under anaerobic conditions for 10 hours to obtain a surface-modified fiber.

[0089] S4. adding the surface-modified fiber prepared in step S3 to tetrahydrofuran containing phosphorus oxychloride, and adding pyridine, after ultrasonic reaction for 3 hours, dropwise adding a tetrahydrofuran solution containing 4,4-diaminodiphenylmethane, the mass ratio of the surface-modified fiber, phosphorus oxychloride, 4,4-diaminodiphenylmethane and pyridine being 10:8:12:3, and reacting at room temperature for 30 hours to obtain a P / N-modified fiber;

[0090] S5. PP, P / N modified fiber and antioxidant were mixed in a mass ratio of 100:20:0.2 and added into a torque rheometer for melt blending. The blending temperature was 190°C, the torque speed was 40r / min, and the blending time was 8min to obtain a flame-retardant PP material.

[0091] Examples 1-5 and Comparative Examples 1-3 were melt-extruded and granulated by a twin-screw extruder, and then experimental specimens were prepared by an injection molding machine for flame retardant performance tests and mechanical property tests.

[0092] Flame retardant performance test: UL-94 vertical combustion test is carried out according to ASTM D635-77 standard, and the self-extinguishing and burning speed of the sample are recorded after the flame is removed; further UL-94 V-0, UL-94 V-1, UL-94 V-2 vertical combustion tests are carried out: the self-extinguishing time of the sample after the flame is removed and the ignition of the absorbent cotton pad are recorded.

[0093] Table 1 Flame retardant performance test

[0094]

[0095] Mechanical properties test: The tensile properties test is carried out in accordance with GB / T1040-2006 standard; the impact properties test is carried out in accordance with GB / T1043-2008 standard.

[0096] Table 2 Mechanical properties test

[0097] Tensile strength (MPa) Elongation at break (%) <![CDATA[Izod impact strength (KJ / m 2 )]]> Example 1 42.6 17.1 13.1 Example 2 44.1 16.6 12.8 Example 3 46.3 15.8 12.9 Example 4 47.5 15.4 12.5 Example 5 46.8 15.2 12.3 Comparative Example 1 45.9 15.4 12.6 Comparative Example 2 38.9 16.2 11.6 Comparative Example 3 35.8 17.8 13.6 pp 32.1 21.6 15.3

[0098] From Table 2, it can be seen that compared with PP, after adding flame retardant, the impact strength of the material is slightly reduced, and the addition of flame retardant reduces the plasticity of the material, but the mechanical property retention rate of the material can basically reach more than 90% of the raw material, which fully meets the mechanical property requirements of the battery shell.

[0099] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a flame-retardant PP material for a battery shell, characterized in that: The following steps are involved: S1. adding the hollow porous titanium dioxide fiber to water and uniformly dispersing it by ultrasonication to obtain a titanium dioxide fiber suspension, adding a magnesium chloride solution to the suspension, and stirring at a constant temperature until the magnesium chloride penetrates into the surface and gaps of the titanium dioxide fiber, and then adding ammonia water to react to obtain a titanium dioxide fiber filled with magnesium hydroxide; S2. adding the titanium dioxide fiber coated with magnesium hydroxide prepared in step S1 to dimethyl sulfoxide, stirring at a certain temperature, then adding sodium bisulfate, stirring and then adding 3,4-dihydroxyphenylalanine, reacting under anaerobic conditions to obtain a surface-modified fiber; S3. adding the surface-modified fiber prepared in step S2 to tetrahydrofuran containing phosphorus oxychloride, and adding pyridine, after ultrasonic reaction, dropwise adding a tetrahydrofuran solution containing 4,4-diaminodiphenylmethane, the mass ratio of the surface-modified fiber, phosphorus oxychloride, 4,4-diaminodiphenylmethane and pyridine being 5-10:3-8:6-12:2-3, and reacting at room temperature to obtain a P / N-modified fiber; S4. Add PP, P / N modified fiber and antioxidant into the torque rheometer in a certain proportion for melt blending to obtain flame retardant PP material.

2. The method for preparing the flame-retardant PP material for battery housing according to claim 1, characterized in that: The preparation method of the hollow porous titanium dioxide fiber comprises the following steps: S11. The butyl titanate was dissolved in acetone, stirred evenly, and polyvinyl pyrrolidone was added and stirred to dissolve to obtain a butyl titanate solution; S12. Remove the glue on the surface of the cotton fiber with a sodium hydroxide solution, then acidify it with a low concentration of acid, add sodium chloroacetate and 1,3-pentanediamine to the acidified cotton fiber, stir for reaction, add the butyl titanate solution prepared in step S1, stir and ultrasonicate, filter, dry and calcine to obtain a hollow porous titanium dioxide fiber.

3. The method for preparing the flame-retardant PP material for battery housing according to claim 2, characterized in that: In the step S11, the mass ratio of butyl titanate, polyvinyl pyrrolidone and acetone is 4-8:0.5-1:8-15.

4. The method for preparing the flame-retardant PP material for battery housing according to claim 2, characterized in that: In step S12, the mass ratio of cotton fiber, sodium chloroacetate, 1,3-pentanediamine and butyl titanate solution is 10:1-2:0.8-1.2:15-20, the calcination parameters are heating at room temperature, the heating rate is 1-1.5°C / min, the end temperature is 650-720°C, and the calcination is continued for 2-3h after reaching the end temperature.

5. The method for preparing the flame-retardant PP material for battery housing according to claim 1, characterized in that: In step S1, the concentration of magnesium chloride is 1-1.2 mol / L, the concentration of ammonia water is 1.2-1.6 mol / L, the temperature of constant temperature stirring is 25-35° C., and the reaction time is 30-45 min.

6. The method for preparing the flame-retardant PP material for battery housing according to claim 1, characterized in that: In step S2, the stirring temperature is 80-100° C. and the reaction time is 10-30 h.

7. The method for preparing the flame-retardant PP material for battery housing according to claim 1, characterized in that: The ultrasonic reaction time in step S3 is 1-3 hours, and the room temperature reaction time is 10-30 hours.

8. The method for preparing the flame-retardant PP material for battery housing according to claim 1, characterized in that: In the step S4, the mass ratio of PP, P / N modified fiber and antioxidant is 100:20-35:0.2-0.8; the blending temperature is 175-190° C., the torque speed is 40-60 r / min, and the blending time is 8-15 min.

9. The flame-retardant PP material for a battery shell prepared by the preparation method according to any one of claims 1 to 8.